2015
DOI: 10.1111/apm.12470
|View full text |Cite
|
Sign up to set email alerts
|

Portal and splanchnic hemodynamics after partial splenic embolization in cirrhotic patients with hypersplenism

Abstract: To assess the acute effects of partial splenic embolization (PSE) on portal and splanchnic hemodynamics in patients with cirrhosis. Ninety-five patients with hypersplenism were included in the study. Duplex examinations were performed before and 3 and 7 days after PSE. Portal and splanchnic hemodynamics including vessel cross-sectional area (CSA), mean flow velocities (cm/s), blood flows (mL/min), Doppler indices as portal congestion index (CI), liver vascular index, hepatic artery and superior mesenteric arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…However, change in spleen volume was significantly correlated with change in serum albumin level. Studies have shown that reduction in spleen volume by PSE reduced portal pressure and flow in the splenic vein, but maintained portal perfusion [18][19][20]. These studies suggest that reduction in splenic arterial flow caused significant reduction in splenic venous flow with minimal decrease in the portal vein flow volume, while the flow of the superior mesenteric vein increased.…”
Section: Discussionmentioning
confidence: 90%
“…However, change in spleen volume was significantly correlated with change in serum albumin level. Studies have shown that reduction in spleen volume by PSE reduced portal pressure and flow in the splenic vein, but maintained portal perfusion [18][19][20]. These studies suggest that reduction in splenic arterial flow caused significant reduction in splenic venous flow with minimal decrease in the portal vein flow volume, while the flow of the superior mesenteric vein increased.…”
Section: Discussionmentioning
confidence: 90%
“…Some previous studies have demonstrated the precise effect of PSE in PVP reduction. 24,25 In addition, clinical trials have shown that endoscopic and endovascular therapies combined with PSE significantly reduced the rate of esophagogastric variceal bleeding and recurrence. 20,26,27 Moreover, splenic artery embolization for patients with cirrhosis and hypersplenism has been reported to improve functional parameters of the liver.…”
Section: Discussionmentioning
confidence: 99%
“…PSE is used to improve liver function, reduce variceal bleeding, treat hepatic encephalopathy, and improve blood cell counts in patients with portal hypertension [7]. In addition, PSE can increase platelet count in patients with hypersplenism from idiopathic thrombocytopenic purpura, thalassemia, idiopathic hypersplenism, and cytopenia caused by anticancer chemotherapy [7][8][9][10]. The improved liver function observed in patients with cirrhosis following PSE is likely related to increased blood flow in the hepatic arterial and superior mesenteric vein [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PSE can increase platelet count in patients with hypersplenism from idiopathic thrombocytopenic purpura, thalassemia, idiopathic hypersplenism, and cytopenia caused by anticancer chemotherapy [7][8][9][10]. The improved liver function observed in patients with cirrhosis following PSE is likely related to increased blood flow in the hepatic arterial and superior mesenteric vein [8]. PSE can arrest variceal bleeding as a result of decreased splenic venous flow into the portal venous system, leading to reduction in mesenteric and colonic venous pressures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation